1998
DOI: 10.1161/01.hyp.31.1.505
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin: A Possible Autocrine or Paracrine Inhibitor of Hypertrophy of Cardiomyocytes

Abstract: Abstract-Adrenomedulhn(AM), a potent vasodllator peptlde, exists m the cardiac ventricle, however, the role of AM m the ventricular tissue remams unknownIn the present study, we mvestlgated the production and secretlon of AM m cultured neonatal rat cardlomyocytes, and we exammed the effect of AM on de novo protein synthesis m these cells by measurmg ['4C] any efforts have been made to clarify the mechanisms of growth regulation of the cardiac myocardmm because of comphcatlons of the heart caused by cardiac hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 32 publications
12
110
0
1
Order By: Relevance
“…In addition, AM has been shown to be synthesized and secreted from cultured cardiac myocytes, mesangial cells, and vascular endothelial and smooth muscle cells (15)(16)(17)(18). It has been reported that both plasma ANP and BNP concentrations in hypertensive patients are higher than those in normotensive controls (19,20), and consistent results were obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, AM has been shown to be synthesized and secreted from cultured cardiac myocytes, mesangial cells, and vascular endothelial and smooth muscle cells (15)(16)(17)(18). It has been reported that both plasma ANP and BNP concentrations in hypertensive patients are higher than those in normotensive controls (19,20), and consistent results were obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, PRA in the patients with MHT was much higher than the upper limit of the normal range and was reduced by antihypertensive treatment. The results of in vitro experiments suggest that angiotensin II is an important factor stimulating the production and secretion of AM in cardiac myocytes and vascular smooth muscle cells (15,18). In any case, further studies are necessary to identify the source and mechanism for the increased plasma AM levels in patients with MHT and EHT.…”
Section: Discussionmentioning
confidence: 99%
“…26 After culturing the cells under the serum-free Dulbecco's modified Eagle's medium containing 10 mg ml À1 insulin, 5 mg ml À1 transferrin and 7 ng ml À1 sodium selenite for 48 h, BAY 41-2272 (10 À6 and 10 À5 mol l À1 ) was then added to the medium to examine the intracellular cGMP elevation.…”
Section: Soluble Guanylate Cyclase and Cardiac Fibrosis H Masuyama Et Almentioning
confidence: 99%
“…In rat mesangial cells, adrenomedullin inhibits mitogenesis even under quiescence and suppresses MAPK activity (52,53). In cultured neonatal rat cardiocytes and cardiac fibroblasts, adrenomedullin suppresses cell growth (54,55). Certain cancer cells do not proliferate in response to adrenomedullin, and some of these cell lines show a growth-inhibitory response with elevation of intracellular cAMP (56).…”
mentioning
confidence: 99%